Pendampingan Penyusunan Laporan Keuangan Berbasis Microsoft Excel pada Bumdes Muda Berkarya - Faricha Royani Musafa; R.A Lailatul Laili; Ramadhani Asa Putra; Nurul Herawati; Atik Emilia Sula; Emi Rahmawati (Senarai Kearifan Lokal Akuntansi: Jurnal Pengabdian Masyarakat, 2026)
AbstractBUMDes Muda Berkarya continues to face challenges in preparing financial reports, particularly regarding cash book recording and financial transaction management, which are still handled manually. This community service initiative aims to assist the Village-Owned Enterprise BUMDes Muda Berkarya in Soket Laok Village, Tragah District, Bangkalan Regency in preparing simple financial reports using a Microsoft Excel application designed for BUMDes financial reporting. The method employed involves mentoring that fosters active and participatory learning among all stakeholders. The outcome of this initiative is the adoption of the Microsoft Excel application developed by the Accounting Department of Trunojoyo Madura University—by BUMDes Muda Berkarya for its financial reporting process, thereby facilitating more structured financial recording and reporting. This activity has enhanced the BUMDes management's ability to prepare financial reports in a more structured manner and supports improved financial management of the enterprise.